Effect of locally delivered doxycycline as an adjunct to scaling and root planing in the treatment of periodontitis in smokers: A systematic review of randomized controlled trials with meta-analysis and trial sequential analysis - Sonia Nath; Shaju Jacob Pulikkotil; Lalli Dharmarajan; Muthukumaraswamy Arunachalam; Kweh Ting Jing (Wolters Kluwer Medknow Publications, 2020)
Background: Scaling and root planing (SRP) for the treatment of periodontitis may be less effective in some patients. This study evaluated the effectiveness of local doxycycline as an adjunct to SRP among smokers with periodontitis compared to SRP alone in randomized controlled trials (RCTs). Materials and Methods: For this systematic review and meta-analysis, PubMed and Scopus databases were searched till November 2018 for English publications. RCTs that compared the effect of local doxycycline adjunct to SRP among smokers with periodontitis were selected. Patient characteristics, disease characteristics, and outcome data on clinical attachment level (CAL) and periodontal probing depth at 1, 3- and 6-month follow-up was extracted. Quality of selected studies was assessed by the revised Cochrane Risk of Bias 2.0 tool. Random effects model and trial sequential analysis were performed. GRADE approach was used to assess the quality of evidence. P > 0.05 was considered as statistically significant. Results: Five trials were included in the review. Local use of doxycycline as an adjunct to SRP was effective in gain of 1.1 mm (0.47-1.74, P = 0.091) in CAL at 6 months calculated from two studies. The evidence was of low quality, and at least a total of 866 patients are required for conclusiveness. Conclusion: Local doxycycline as an adjunct to SRP significantly improved clinical attachment in smokers with periodontitis and can be recommended. Studies are required with long-term follow-up and patient-related outcome data.